2013
DOI: 10.1093/icvts/ivs518
|View full text |Cite|
|
Sign up to set email alerts
|

Cavopulmonary anastomosis without cardiopulmonary bypass†

Abstract: Off-pump bidirectional Glenn operation without caval decompression is a safe, simple and more economic procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…In our study only 7.8% of our patients had undergone previous surgeries while it was higher in other studies by Talwar et al 8 (15.3%), Reddy et al 11 (62%), Mostafa et al 20 (16%) Hussain et al 14 (32.4%) and Alsoufi et al 9 (81%). Only one of our patients underwent Pulmonary Artery banding.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In our study only 7.8% of our patients had undergone previous surgeries while it was higher in other studies by Talwar et al 8 (15.3%), Reddy et al 11 (62%), Mostafa et al 20 (16%) Hussain et al 14 (32.4%) and Alsoufi et al 9 (81%). Only one of our patients underwent Pulmonary Artery banding.…”
Section: Discussioncontrasting
confidence: 57%
“…The early hospital mortality in our study group is 10.4%. The hospital mortality rates varies from 0% to 33% in various studies reported by Tanoue et al 22 (0.9%), Liu et al 12 (0%), Mostafa EA et al 20 (4%), Reddy Kandakure et al 16 (2.14%), Warrier et al (3.6%), Tireli et al 33 (3.3%), Lapar et al 7 (0.9%), Kogon et al 10 (2%), Jaquiss et al 36 (0%), Reddy et al 11 (4.8%), Talwar et al 8 (1.86%), Deebis et al 13 (7.4% in the CPB group, 10.5% in the non‐CPB group) and Azzolina et al 9 (33%).…”
Section: Discussionmentioning
confidence: 92%
“…The mean internal venous pressure on clamping the superior vena cava was 37.07 ± 7.12 mmHg in the non‐shunt group and 24 ± 4.4 mmHg in the shunt group. There were no major neurological complications apart from treatable convulsions in one patient in the non‐shunt group and two patients in the shunt group …”
Section: Discussionmentioning
confidence: 93%
“…The authors did not find any significant differences in the postoperative parameters in both groups. Recently, Mostafa et al prospectively compared off‐CPB BDG with and without a veno‐atrial shunt. The early hospital mortality was 4% in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusion of the SVC without a temporary shunt can lead to decreased cerebral blood flow and risks injury to the brain. 68 Intra-cranial or orbital hematomas have not been previously reported in BCPS performed with SVC clamping. The physiology and duration in our patient are similar to a BCPS performed with clamping of the SVC.…”
Section: Discussionmentioning
confidence: 95%